New titanium complexes containing an amidinate-imide supporting ligand set: Cyclopentadienyl, alkyl, borohydride, aryloxide, and amide derivatives - Stewart, P; Blake, A; Mountford, P (1998)
A range of chloride metathesis reactions of the monomeric titanium N,N′-bis(trimethylsilyl)-benzamidinato-imido complexes [Ti(NBut){(4-C6H4R)C(NSiMe3) 2}Cl(py)2] (R = H (1) or OMe (2)) are described. Thus, reaction of 1 or 2 with LiC5H5 gave the half-sandwich compounds [Ti(NBut){(4-C6H4R)C(NSiMe3) 2}(η-C5H5)] (R = H (3) or OMe (4)). Reaction of 1 with LiCH2-SiMe3 or LiCH(SiMe3)2 gave the 14-electron, first fully characterized group 4 imido-alkyl derivatives [Ti(NBut){PhC(NSiMe3)2}{CH(R)SiMe 3}(py)] (R = H (5) or SiMe3 6)). For comparative purposes, the 16-electron half-sandwich imido-alkyl complex [Ti(NBut)(η-C5Me5)(CH2SiMe 3)(py)] (7) was prepared from LiCH2SiMe3 and [Ti(NBut)(η-C5Me5)Cl(py)]. Reaction of 1 with LiBH4 gave the η3-borohydride derivative [Ti(NBut){PhC(NSiMe3)2}(η 3-BH4)(py)] (8) while treatment of 1 with LiN(SiMe3)2, LiO-2,6-C6H3R2 (R = Me or But), or LiPhC(NSiMe3)2, gave the corresponding aryloxide, amide, or bis(benzamidinate) titanium imido complexes [Ti(NBut){PhC(NSiMe3)2}{N(SiMe 3)2}(py)] (9) [Ti(NBut){PhC(NSiMe3)2}-(O-2,6-C 6H3R2)(py)] (R = Me (10) or But (11)), or [Ti(NBut){PhC(NSiMe3)2}2(py)] (13). Activation parameters for the concerted, restricted rotation of the aryloxide and benzamidinate ligands in 11 are reported and point to a dissociatively activated mechanism. The X-ray structures of 5 and 7 have been determined.